ASSESSING THE ROLE OF TOURISM AS A PATH-WAY TOWARDS THE DEVELOPMENT OF NIGERIA - GUNDELE, ASHIM O. (ITB Journal Publisher, LPPM ITB, 2010)
Before the emergence of tourism as a main sector in Nigeria, crude oil has been the chief source of Nigeria revenue also the most valuable treasure on the Nigerian economy. Remarkable efforts have been made by the past and current leaders regarding the development of tourism in Nigeria. However, description alone not necessitate meaningful and, unless integrated with effective planning, critical evaluation and assessment coupled with the view of achieving sustainability. This study suggests how tourism can be regionally planned based on the resources in order to improve the economic status of Nigeria using Destination Zones Identification to apprise the potential destinations within the 4 (four) main divisions of Ogun state, South-Western Nigeria, also suggest alternative ways and strategies towards promoting tourism in Nigeria and other developing countries.